Peter Winch on the Concept of Persuasion. (20th May 2015) - Durante, Raffaele
Abstract: The aim of the paper is to give an account of Peter Winch's conception of persuasion . According to Winch, persuasive arguments are those carried out in order to let an interlocutor with a different world picture, and thus a different epistemology, see the point of our practices and beliefs. This involves convincing him of the fact that his way of thinking is neither unique nor better than other ones. Furthermore, given that there is no guarantee that one can arrive at a complete understanding of alien practices, persuasion may, in some cases, aim at the impossible.